A coupled thermal-hydraulic-mechanical modeling and evaluation of geothermal extraction in the enhanced geothermal system based on analytic hierarchy process and fuzzy comprehensive evaluation. (15th January 2020) - Guo, Tiankui; Tang, Songjun; Sun, Jiang; Gong, Facheng; Liu, Xiaoqiang; Qu, Zhanqing; Zhang, Wei
Highlights: An improved thermal-hydraulic-mechanical coupling model was established. Evaluation index system for geothermal energy development effect was put forward. Evaluation method for EGS based on AHP and FCE was proposed. Well arrangement patter and development parameters were optimized. Abstract: In the paper, the thermal-hydraulic-mechanical (THM) coupling model is improved by considering more factors, and a comprehensive evaluation method is proposed to optimize the heat extraction way. The thermal extraction characteristics in the Enhanced Geothermal System (EGS) and their influence factors were modeled by several researchers, and various evaluation and optimization methods were established. However, by comparing various thermal-hydraulic-mechanical (THM) models, we find that these factors of THM models are not considered comprehensively, and current EGS evaluation focuses on the individual index, the multi-objective evaluation index system of EGS has not been proposed, and a comprehensive evaluation system considering multiple indexes has not been established yet. In this study, a thermal-hydraulic-mechanical coupling model, considering matrix, fractures and changes in physical parameters of rock and fluid, was established for optimizing the EGS. The evaluation index system, including the operation life, the thermal breakthrough time, the average heat production rate, the total heat recovery factor and the re-injection factor, were presented. And the comprehensive optimization method based on analytic hierarchy process (AHP) and fuzzy comprehensive evaluation (FCE) of EGS were proposed. The model is verified by two analytical solutions. Moreover, the model was solved by finite element method (FEM) to optimize various programs of developing the EGS. In this paper, the performances of different geothermal extraction methods are compared and the different extraction parameters are optimized. The results show that the optimized geothermal mining method has better effect than that before optimization. The orthogonal test shows the optimal case of 5 fractures, the fracture permeability of 10D, the well spacing is 400 m and the production pressure draw-down of 20 MPa. The research results provide an accurate and effective method to optimize the development mode of geothermal resources, which is conductive to improve the geothermal energy efficiency.